Comparative Implementation of Legal Systems between Indonesia and Yemen - Aulia, Ajeng Hijiratul; Latif, Abdul; Aditya, Muhammad; Oktaviany, Nadilla; Hidayati, Sri; Putera, Muhammad Luthfi Setiarno (Universitas Pahlawan Tuanku Tambusai, 2024)
The legal system is a framework of rules governing human behavior in society to ensure justice, order, and welfare. This study examines the legal systems of Indonesia and Yemen, highlighting their differences and similarities and their impact on society and political structures. Indonesia adopts a mixed legal system combining legislation, customary law, and Islamic principles, influenced by cultural pluralism and Dutch colonial heritage. In contrast, Yemen's legal system is predominantly based on Sharia law, with formal courts emphasizing Islamic principles as their primary foundation.Using a normative legal research method with a literature review approach, the study draws data from books, scholarly journals, prior research, and relevant articles. Findings reveal Indonesia's pluralistic approach to law reflects its diverse cultural, religious, and ethnic landscape, while Yemen's system is rooted in Islamic law, reflecting a more uniform legal framework. Despite structural differences, both countries acknowledge the central role of Islamic law in their legal systems. This research contributes to a deeper understanding of the legal dynamics in both nations, offering insights for future legal development and enriching the global discourse on legal pluralism.